Recurrent Glomerular Disease after Kidney Transplantation: Diagnostic and Management Dilemmas. Issue 11 (November 2021) - Uffing, Audrey; Hullekes, Frank; Riella, Leonardo V.; Hogan, Jonathan J.
Abstract : Recurrent glomerular disease after kidney transplant remains an important cause of allograft failure. Many of the different entities post-transplant still suffer from incomplete knowledge on pathophysiology, and therefore lack targeted and effective therapies. In this review, we focus on specific clinical dilemmas encountered by physicians in managing recurrent glomerular disease by highlighting new insights into the understanding and treatment of post-transplant focal segmental glomerulosclerosis, membranous nephropathy, atypical hemolytic uremic syndrome, C3 glomerulopathy, amyloid light-chain (AL) amyloidosis, and IgA nephropathy.